2020
DOI: 10.3389/fphar.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1/Nitric Oxide Ratio as a Predictive Factor of Response to Therapy With Terlipressin and Albumin in Patients With Type-1 Hepatorenal Syndrome

Abstract: Background and Purpose: Predictors of response to type-1 hepatorenal syndrome (HRS) therapy are urgently needed. This study's purpose is to evaluate the proposed predictors in these patients.Methods: Forty-two type-1 HRS patients with cirrhosis were treated with albumin and terlipressin. Clinical, biochemical, and demographic parameters taken at the onset of therapy and changes in endothelin-1/nitric oxide (ET-1/NO) ratio during therapy were analyzed to check their predictive value.Results: Response to treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Randomized trials with low-dose terlipressin or alternate day terlipressin therapy may be utilized to reduce the adverse effects of terlipressin in patients with ACLF. Endothelin-1/Nitric oxide ratio aid in predicting response to terlipressin therapy 28 . Serum endothelin levels, nitric oxide, lactate dehydrogenase levels may be used to monitor and predict the ischemic adverse events of terlipressin.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials with low-dose terlipressin or alternate day terlipressin therapy may be utilized to reduce the adverse effects of terlipressin in patients with ACLF. Endothelin-1/Nitric oxide ratio aid in predicting response to terlipressin therapy 28 . Serum endothelin levels, nitric oxide, lactate dehydrogenase levels may be used to monitor and predict the ischemic adverse events of terlipressin.…”
Section: Discussionmentioning
confidence: 99%
“…In previous works [ 17 , 22 ], we demonstrated that the pyruvate tolerance test is a good tool to assess the liberation of HGO in the fasting state. G6Pase can control hyperglycemia because it determines the production of glucose released from gluconeogenesis and glycogenolysis [ 23 ]; therefore, inhibition of this rate-limiting enzyme is a target to treat hyperglycemia in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials with low dose terlipressin or alternate day terlipressin therapy may be utilized to reduce the adverse effects of terlipressin in patients with ACLF. Endothelin-1/Nitric oxide ratio aid in predicting response to terlipressin therapy [30]. Serum endothelin levels, nitric oxide, lactate dehydrogenase levels may be used to monitor and predict the ischemic adverse events of terlipressin.…”
Section: Discussionmentioning
confidence: 99%